Formation of friable embryogenic callus in cassava is enhanced under conditions of reduced nitrate, potassium and phosphate. - Yoshinori Utsumi; Chikako Utsumi; Maho Tanaka; Vu The Ha; Akihiro Matsui; Satoshi Takahashi; Motoaki Seki (PLoS ONE)
Agrobacterium-mediated transformation is an important research tool for the genetic improvement of cassava. The induction of friable embryogenic callus (FEC) is considered as a key step in cassava transformation. In the present study, the media composition was optimized for enhancing the FEC induction, and the effect of the optimized medium on gene expression was evaluated. In relative comparison to MS medium, results demonstrated that using a medium with reducing nutrition (a 10-fold less concentration of nitrogen, potassium, and phosphate), the increased amount of vitamin B1 (10 mg/L) and the use of picrolam led to reprogram non-FEC to FEC. Gene expression analyses revealed that FEC on modified media increased the expression of genes related to the regulation of polysaccharide biosynthesis and breakdown of cell wall components in comparison to FEC on normal CIM media, whereas the gene expression associated with energy flux was not dramatically altered. It is hypothesized that we reprogram non-FEC to FEC under low nitrogen, potassium and phosphate and high vitamin B1. These findings were more effective in inducing FEC formation than the previous protocol. It might contribute to development of an efficient transformation strategy in cassava.